Crusades.
1 online resource.
Keywords: Crusades covers the seven hundred years from the First Crusade (1095-1102) to the fall of Malta (1798) and draws together scholars working on theatres of war, their home fronts and settlements from the Baltic to Africa and from Spain to the Near East and on theology, law, literature, art, numismatics and economic, social, political and military history. Routledge publishes this journal for The Society for the Study of the Crusades and the Latin East. Particular attention is given to the publication of historical sources - narrative, homiletic and documentary - but studies and interpretative essays are welcomed too. Crusades also incorporates the Society's Bulletin. The editors are Professor Benjamin Z. Kedar, Hebrew University of Jerusalem, Israel; Professor Jonathan Phillips, Royal Holloway, University of London, UK; Iris Shagrir, The Open University of Israel; and Nikolaos G. Chrissis, Democritus University of Thrace, Greece.